Resilience and Inclusion: Fostering Non-Violence in Education in Cameroon (London Journal of Research In Humanities and Social Sciences, 2025)
The study investigates resilience and inclusive practices by non-violence education in Cameroon as the focal point. The essence of the study was to investigate the relationship between resilience, inclusion and non-violence within the educational context in Cameroon. It has been reflecting how the victims can navigate the challenge with resilience by non-violence. It emanated from a project on the effects of violence on students learning in Cameroon with the research question on their survival ability of such abuses. The study employed a cross-sectional design with a quantitative approach of data collection and processing. The sample participants comprised (n = 924) students randomly selected from eight secondary schools in one region of Cameroon with four schools chosen from the urban center and four others from the rural centre. These schools were used as the primary source of data collection for the study. The collection of data was undertaken with questionnaires that have been tested and validated through multinational and regional organizations, pilot studies, and different institutions. The structured questionnaires were used to elicit data from the participants. The collected data was analysed using JAMOVI. The study's findings show high levels of violence with both genders suffering equally from the scourge. Furthermore, the male gender in the findings from some of the variables are more subservient and more affected by sexual violence, besides other violence strands such as structural, psychological, environmental and physical violence. These findings therefore introduce diverse probabilities and hypotheses. The subservient of males to sexual violence reduces schools to arenas of illicit sexual activities thereby compromising the learning, social justice and global values for the students. Looking forward, agencies should provide support to educational institutions in their efforts to assist students who are confronted with violence through the implementation of resilience, capacity building and inclusive practices. These practices will help in addressing discrimination among school communities, preventing violence, and cultivating an effective learning environment for all students, irrespective of their background. The advancement of inclusion and resilience signifies a more efficacious approach to addressing school violence and establishing a secure environment for all.
Keywords: curriculum development; Constructivism; Philippine Education; student-centered; Lacking animal protection in Georgia; animal ethics as a moral deficit in the 21st century; cultural indifference in the Transcaucasus; lack of awareness; Social Isolation; Connected Generation; Digital Communication; Online Communities; Social Media Impact; Psychological Well-being; Digital Age Loneliness; Virtual Relationships; Technology and Human Interaction; Creative writing; idioms; language proficiency; sounding native like; vocabulary; inclusive practice; non-violence; quality education